2019
DOI: 10.1097/aud.0000000000000808
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Output and Low-Frequency Limitations of B71 and B81 Clinical Bone Vibrators: Implications for Vestibular Evoked Potentials

Abstract: Objectives: Bone-conducted vestibular evoked myogenic potentials (VEMPs) are tuned to have their maximum amplitude in response to tone bursts at or below 250 Hz. The low-frequency limitations of clinical bone vibrators have not been established for transient, tone burst stimuli at frequencies that are optimal for eliciting VEMPs. Design: Tone bursts with frequencies of 250 to 2000 Hz were delivered to B71 and B81 bone vibrators and their output was exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 34 publications
3
18
0
Order By: Relevance
“…One advantage of bone-conducted cVEMPs is that their thresholds are lower than air-conducted cVEMPs when quantifying stimulus level with units relative to the auditory perceptual detection thresholds of the eliciting stimulus, or dB nHL (McNerney and Burkard 2011;Welgampola et al 2003). Additional advantages of bone-conducted cVEMPs include less risk of noise-induced damage (Portnuff et al 2017), they are less affected by conductive hearing loss than air-conducted cVEMPs (Mahdi et al 2013), and bone conduction may be an inherently more efficient otolith stimulus (Clinard et al 2019;Curthoys 2010). Bone-conducted cVEMPs recorded from the SCM are believed to reflect primarily saccular activity, even though the utricle is also stimulated; animal and human-lesion reports indicate that cervical VEMPs represent primarily saccular activity, innervated by the inferior vestibular nerve, and ocular VEMPs reflect primarily utricular activity, innervated by the superior vestibular nerve (Curthoys 2010;Curthoys et al 2014;Iwasaki et al 2009;Manzari et al 2010).…”
Section: Effects Of Emg Activation On Amcvemp Amplitudementioning
confidence: 99%
“…One advantage of bone-conducted cVEMPs is that their thresholds are lower than air-conducted cVEMPs when quantifying stimulus level with units relative to the auditory perceptual detection thresholds of the eliciting stimulus, or dB nHL (McNerney and Burkard 2011;Welgampola et al 2003). Additional advantages of bone-conducted cVEMPs include less risk of noise-induced damage (Portnuff et al 2017), they are less affected by conductive hearing loss than air-conducted cVEMPs (Mahdi et al 2013), and bone conduction may be an inherently more efficient otolith stimulus (Clinard et al 2019;Curthoys 2010). Bone-conducted cVEMPs recorded from the SCM are believed to reflect primarily saccular activity, even though the utricle is also stimulated; animal and human-lesion reports indicate that cervical VEMPs represent primarily saccular activity, innervated by the inferior vestibular nerve, and ocular VEMPs reflect primarily utricular activity, innervated by the superior vestibular nerve (Curthoys 2010;Curthoys et al 2014;Iwasaki et al 2009;Manzari et al 2010).…”
Section: Effects Of Emg Activation On Amcvemp Amplitudementioning
confidence: 99%
“…34 Previous cVEMP tuning literature has used transient tonebursts, and although these tonebursts have spectral energy centered on the stimulus frequency (e.g., 500 Hz), they have spectral splatter, or energy distributed over a wide range of frequencies resulting from transient distortion. 35 Amplitude-modulated tones, however, have greater frequency specificity as they contain energy only at the carrier frequency and two sidebands ± the modulation frequency. It is possible that the more focused spectral energy of AM tones could reveal larger tuning differences in pathological populations than has been previously reported with cVEMPs elicited by transient tonebursts.…”
Section: Discussionmentioning
confidence: 99%
“…BCV is a viable alternative mode of stimulation for eliciting VEMP responses. Various bone vibrators have been used to elicit VEMPs, such as tap hammer ( 9 , 11 ), mini-shaker 4810 ( 3 , 12 ), B-70B ( 13 ), V201 ( 14 ), Radioear B71 ( 6 , 15 ), and Radioear B81 ( 16 , 17 ). Radioear B71 and B81 are universal components for the testing of hearing levels using the bone conduction method.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that relative to the B71, the B81 vibrator has higher maximum output levels and lower distortion to be used in pure-tone audiometry ( 18 ). However, Clinard et al ( 16 ) reported that the maximum output levels of the B81 vibrator were equivalent to B71 at 500 Hz (stimuli were tone bursts with a fixed duration of 8 ms). Romero et al ( 19 ) used the same frequency and duration of stimuli (500 Hz, rise-plateau-fall times: 4-0-4 ms), as Clinard et al showed no statistically significant differences between the amplitudes of the B71- and B81-cVEMP.…”
Section: Introductionmentioning
confidence: 99%